2010
DOI: 10.1111/j.1465-7295.2009.00222.x
|View full text |Cite
|
Sign up to set email alerts
|

Monetary Policy Regime Shifts: New Evidence From Time‐varying Interest Rate Rules

Abstract: "We estimate forward-looking interest rate rules for five large Organization for Economic Cooperation and Development economies, allowing for time variation in the responses to macroeconomic conditions and in the variance of the policy rate. Conventional constant parameter reaction functions likely blur the impact of (1) model uncertainty, (2) conflicting objectives, (3) shifting preferences, and (4) nonlinearities of policymakers' choices. We find that monetary policies followed by the United States, the Unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 47 publications
3
18
0
Order By: Relevance
“…The decrease of inflation persistence has been attributed to a more aggressive monetary policy stance in the US (Davig and Doh, 2008) and to the implementation of credible monetary policy regimes such as inflation targeting elsewhere (Benati, 2008). The linkage between changes in inflation dynamics and monetary policy is further corroborated by evidence about structural changes in monetary policy itself (Baxa et al, 2010;Boivin, 2006;Kim and Nelson, 2006;Koop et al, 2009;Sims and Zha, 2006;Trecroci and Vassalli, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The decrease of inflation persistence has been attributed to a more aggressive monetary policy stance in the US (Davig and Doh, 2008) and to the implementation of credible monetary policy regimes such as inflation targeting elsewhere (Benati, 2008). The linkage between changes in inflation dynamics and monetary policy is further corroborated by evidence about structural changes in monetary policy itself (Baxa et al, 2010;Boivin, 2006;Kim and Nelson, 2006;Koop et al, 2009;Sims and Zha, 2006;Trecroci and Vassalli, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Besides the time-varying coefficient property, their study also considered the uncertainty included in the forecasts of future inflation and output gap. Wesche (2003) performed a time-varying coefficient Taylor rule analysis for the countries considered in Trecroci and Vassalli (2006). He reached a similar conclusion using a Markov-switching model with independent switching processes for the time-varying parameters of the Taylor rule and variances of disturbances.…”
Section: Selective Literature Reviewmentioning
confidence: 85%
“…In the time-varying coefficient framework, many studies have focused just on the monetary-policy reaction function or the Taylor rule. Trecroci and Vassalli (2006), for example, estimated forward-looking Taylor rules for the UK, Germany, France, Italy and the U.S., using the Kalman filter. They demonstrated that the countries analyzed had different interest rate rules and that time-varying Taylor rules are preferred when compared to fixed parameter rules for capturing the variations in the policy rates.…”
Section: Selective Literature Reviewmentioning
confidence: 99%
“…Orphanides and Williams (2005) and Sims and Zha (2006) also document time-variation in the parameters of Taylor rules using a VAR model. Elkhoury (2006), Kuzin (2006), and Trecroci and Vassalli (2006) shows that TVP of Taylor rules outperform Taylor rules with fixed parameters for a substantial number of developed and non-developed countries. Jalil (2004), Boivin and Giannoni (2006), and Kim and Nelson (2006) use the Kalman Filter to illustrate that parameters of the Taylor rule change gradually over time.…”
Section: Review Of Literaturementioning
confidence: 99%